2020
DOI: 10.29313/amwaluna.v4i2.5869
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF Al-HISBAH IN IMPLEMENTATION OF BUSINESS ETHICS IN TRADITIONAL MARKETS

Abstract: This study aims to analyze the implementation of business ethics in traditional markets and analyze the role of al-Hisbah in the implementation of business ethics in the Wonokromo traditional market in Surabaya. This type of research is field research. The data collection methods are observation, interview, and study literature. The research result implies information about the traditional market sellers' understanding of business ethics that very diverse. Although some sellers do not know theoretically about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This concept brings a deep ethical touch, ensuring that every step in economic activity is accompanied by genuine fairness and brilliant transparency. The market watchdog institution adhering to al-Hisbah is expected to act as a loyal guardian, overseeing every corner of economic activity to ensure that the distribution of wealth and opportunity is truly evenly distributed, like the sun illuminating the world with its fair light (Anwar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This concept brings a deep ethical touch, ensuring that every step in economic activity is accompanied by genuine fairness and brilliant transparency. The market watchdog institution adhering to al-Hisbah is expected to act as a loyal guardian, overseeing every corner of economic activity to ensure that the distribution of wealth and opportunity is truly evenly distributed, like the sun illuminating the world with its fair light (Anwar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the sustainability of quality and halal products, an official institution that is professional and authorized to enforce the rules is needed. This is so that consumers get a guarantee that the products they consume have met the elements of quality and halal (Anwar, et al, 2022). In addition to the important role of quality assurance institutions and halal certification, the role of the government to continue to improve the competitive advantage of small and medium companies such as the tempeh industry is very necessary.…”
Section: Quality Of Tempe Pejeruk Abian Based On Consumer Evaluation ...mentioning
confidence: 99%
“…The results of the analysis revealed that tremendous successes have been achieved, but despite these successes, some important obstacles such as insufficient staffing and funding, lack of working tools and corruption affect the smooth functioning of these institutions. Anwar et al (2020), on the other hand, investigated the role of Hisbe in the practice of business ethics in the Wonokromo neighborhood market in Surabaya, Indonesia. As a result of the research, it was determined that although some sellers do not have theoretical knowledge of business ethics, they apply ethical business values because they obey the religious values taught by their families, while others do not practice these even though they know about religious values.…”
Section: Literature Reviewmentioning
confidence: 99%